A nitrogen doped carbonized metal–organic framework for high stability room temperature sodium–sulfur batteries. Issue 32 (27th July 2016) - Chen, Yu-Ming; Liang, Wenfeng; Li, Si; Zou, Feng; Bhaway, Sarang M.; Qiang, Zhe; Gao, Min; Vogt, Bryan D.; Zhu, Yu
Abstract : A nitrogen-doped carbonized metal–organic framework was utilized for room temperature sodium sulfur batteries. The cZIF-8/S composite electrode exhibited good cyclability over 250 cycles at 0.2C with a specific capacity of 500 mA h g −1 . Abstract : A nanoporous nitrogen doped carbon matrix was prepared by carbonization of metal–organic framework zeolitic imidazolate framework (ZIF-8) precursors. The doped carbon matrix was melt-infiltrated with sulfur to form a carbonized ZIF-8/S composite. The composite material exhibited good performance as the cathode for room-temperature sodium–sulfur battery (Na–S) systems. A reversible specific capacity of around 1000 mA h g −1 could be achieved at a rate of 0.1C; and a reversible specific capacity of 500 mA h g −1 was obtained at a rate of 0.2C after 250 cycles. The good performance of the Na–S battery could be attributed to the synergistic effect from the nanoporosity of the carbon matrix and the high nitrogen-doping content ( ca. ∼18 at%). These attributes enhanced the entrapment of the sulfur molecules inside the carbon matrices.